Effect of Laser Shock Processing and Aluminizing on Microstructure and High-Temperature Creep Properties of 321 Stainless Steel for Solar Thermal Power Generation - Wei Li; Huang Huang; Dongliang Xu; Jian Chen; Lu Zuo; Guozhi Ma; Jianjun He; Cong Li; Zhuoyin Peng; Yanjie Ren; Sheng-de Zhang (International Journal of Photoenergy)
The aluminized layer of 321 stainless steel was treated by laser shock processing (LSP). The effects of constituent distribution and microstructure change of the aluminized layer in 321 stainless steel on creep performance at high temperature were investigated. SEM and EDS results reveal that aluminized coating is mainly composed of an Al2O3 outer layer, the transition layer of the Fe-Al phase, and the diffusion layer. Additionally, LSP conducted on coating surface not only improves the density of the layer structure, resulting in an increment on the bonding strength of both infiltration layer and substrate, but also leaves higher residual compressive stress in the aluminized layer which improves its creep life effectively. Experimental results indicate that the microhardness of the laser-shocked region is improved strongly by the refined grains and the reconstruction of microstructures. Meanwhile, the roughness and microhardness of aluminized steel are found to increase with the laser impact times. On the other hand, the intermetallic layers, whose microstructure is stable enough to inhibit crack initiation, reinforce strength greatly. The anticreep life of aluminized sample with three times LSP was increased by 232.1% as compared to aluminized steel, which could attribute to the increased dislocation density in the peened sample as well as the decrease of creep voids in size and density.